PENDIDIKAN POLRI SEBAGAI PEMBANGUN POLISI SIPIL (STUDI PADA AKADEMI KEPOLISIAN) - Subagyo, Subagyo (Faculty of Social Science, Universitas Negeri Semarang, 2012)
Police at this time not only have the duty as a â€œcrime hunterâ€ and â€œlaw enforcementâ€, but they are required to act as a â€œproblem solving oriented team, maintaining order officers, public servant, public observer and chief executive officerâ€ who are solid in pluralism and social problems in the community. That is part of the efforts to change the old culture of police officers and build civilian character of police. Building a new culture can be started by setting up Police Academy officer with civilian character. Departing from the strategic issues, empirical research on the Police Academy Tarun and devices that contribute to the development of civilian police as the educational system , training and care at the Police Academy are required.Problems discussed in this research are: (1) How far the Police Academy Taruna has an understanding on civilian police? (2) how much education / teaching contributed to the development of civilian police? (3) How much training gave effect on the development of civilian police? (4) how parenting affects the development of the civilian police? The purpose of this study are: (1) Knowing the understanding of the Police Academy Taruna on Civilian Police; (2) Knowing that education / teaching contributed to the development of civilian police, (3) Knowing that training influence on the development of civilian police, (4) Knowing that parenting influence the development of civilian police.This study uses a quantitative approach. Target of the research is the Police Academy Taruna level II and III. Samples of the research is conducted by using stratified proportional random sampling. The independent variablecomprised three variables, namely Education / Teaching, training, and parenting. Dependent variable is the Civilian Police. The data collection wa done by using a questionnaire, collecting the relevant documents and interviews. Data were analyzed with regression techniques. Results showed that education / teaching, training and parenting together contribute positively to the development of the Civilian Police with significance level 0.05 with F = 23.916 count is greater than the F table = 3.943. It can be concluded that the education / teaching, training and parenting give a positive contribution to the process of building a civilian character to Police Academy Taruna. Based on the results of these studies, it is suggested that in order to support the development of civilian police to the Police Academy Taruna in Indonesia, it is required a process of education / teaching, training and nurturing that consistently have to really put forward the principles that form a picture of civilian police, so that in the future, these three things can be a guidance / reference in creating the Police Academy Tarun with police civilian character.